Distance education in portuguese-speaking countries: The case of Brazil, Mozambique and Cape Verde - Silva, Maria Aparecida da (2014)
This article aims to identify and catalog documentation relating to Distance Education in Brazil, Mozambique and Cape Verde, through literature and documents. In the case of Brazil, we identified a large production. Mozambique and Cape Verde expressing scant literature production, with emphasis on historical facts and legal frameworks. Be checked that the search for conceptual understanding and trajectory of DE is presented as relevant for those seeking careers in this field element because it explains the different types of approaches and different educational contexts.